2014
DOI: 10.4172/2157-7110.1000402
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Sugar Extraction from Date Palm (Phoenix dactylifera L.) Fruits

Abstract: In date syrup manufacturing, date fruits (Phoenix dactylifera L.) are mixed with a suitable amount of water with heating at a temperature greater than 70°C for about 1 h. These conditions are not satisfactory for extraction greater amount of liquid sugar (date syrup). In addition, overheating for an extended period could damage nutritious materials and changes product's color. In this study, pectinase/cellulase enzymes and sonication processes were used to achieve maximum syrup extraction from a date variety (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
4
8
1
Order By: Relevance
“…This result confirms the previous funding that concluded that there is good potential and a possibility to produce syrup from date fruits for use as a replacement of sucrose in food products (El-Sharnouby et al, 2014).…”
Section: Sensory Evaluationsupporting
confidence: 92%
See 1 more Smart Citation
“…This result confirms the previous funding that concluded that there is good potential and a possibility to produce syrup from date fruits for use as a replacement of sucrose in food products (El-Sharnouby et al, 2014).…”
Section: Sensory Evaluationsupporting
confidence: 92%
“…The ash contents of all the sorghum flakes analyzed in our study were higher than those of white and red sorghum flakes, whereas the fat contents were lower. The high level of ash in the flakes in this study referred to the use of date syrup, which found to be a good source of macro elements such as calcium, phosphorus, potassium, magnesium (El-Sharnouby et al, 2014).…”
Section: Nutritional and Chemical Compositionmentioning
confidence: 80%
“…This value is slightly higher than that cited by [24] which gives a content of 11.98% for the dry variety 'Mech Deglet, and the one given by [25] for the "h'chef" category of Adar region (which is around 9.02%). However, it is clear from the data obtained that moisture content of the analyzed dates is very close to the recorded average of 15% for the semi-dry Saudi "Reziz" date varieties [26].…”
Section: Physicochemical Characterization Of "H'chef" Date Pulp From Deglet-noursupporting
confidence: 70%
“…The development of dates is classified into four stages: stage 1: 'Kimiri' stage, stage 2: 'Khalal' stage, stage 3: 'Rutab' stage and stage 4: 'Tamer' stage. The tamer stage is the final stage of maturation, when the date has dried to a fairly firm consistency with a darker color 11 .…”
Section: Introductionmentioning
confidence: 99%